Use of genetically informed evidence‐based prevention science to understand and prevent crime and related behavioral disorders - Gajos, Jamie M. (Criminology & public policy, 2016)
n this article, we outline the potential ways that genetic research can be used to inform the development, testing, and dissemination of preventative interventions. We conclude by drawing attention to how the incorporation of genetic variables into prevention designs could help identify individual variability in program effectiveness and thereby increase program success rates.